Tantangan Pengembangan Kurikulum Pendidikan Islam dan Strategi Pengembangannya dalam Menghadapi Tuntutan Kompetensi Masa Depan - Lalu Abdurrahman Wahid; Tasman Hamami (J-PAI: Jurnal Pendidikan Agama Islam, 2021)
Islamic education is currently faced with complex challenges, both internal and external. The problem is how Islamic education is able to respond to the challenges and demands that arise due to these factors. Islamic education needs to seek a strategy so as not to be left behind in formulating a relevant curriculum and able to compete with the demands of changing times. The purpose of this study is to provide information regarding the challenges and demands faced by contemporary Islamic education and strategies to respond to them through curriculum development. This article is included in a qualitative study based on library research. The results show that the challenges faced by Islamic education today come from the internal and external areas of Islamic education. The internal challenges that must be achieved by Islamic education are the achievement of eight national education standards, the growth of Indonesia's population which grows the demographic bonus, and character issues. Islamic education is required to prepare human resources in accordance with the demands of the competence of the times so as to produce alumni who survive and are able to compete in the era of globalization. The external challenges facing Islamic education are more future-oriented challenges. Among them, Islamic education is required to prepare for future needs, relevant to community problems, advances in technology and information, the growth of the creative and cultural sector, and the internationalization of education such as World-class University.